Os indesejáveis: agentes públicos e a gestão da mobilidade de trecheiros e pessoas em situação de rua - Freitas, Cledione Jacinto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The state officials attention given to roamers and people on the streets is becoming increasingly subsidized by an arsenal of standards, guidelines, strategies, institutions, professional, political, to account for the various facets of nomadic and city life. For this reason, the research aimed to investigate how these officials responsible for public welfare office dealt with roamers and people on the streets and conceived this way of life. Imported mainly identify practices and interventions in roamers way of life and people on the streets seeking to disqualify the nomadism that took as a reprehensible way of life or that generated suffering and therefore, needed to be avoided. Interested also understand how, by the look of professional social work, produces the figure of the undesirable from abroad, that needs to be moved to other spaces through public assistance policies. The research took place in a city of approximately one hundred thousand inhabitants in the western region of São Paulo. This city is located in an important roamers circulation corridor formed by the intersection of trunk roads linking the north of the state to the Paraná and the west of the State to the eastern region, which is the capital. The methodology used was ethnography in Psychology with participant observation. We follow the work of the city's team, made up of social workers, psychologists and mid-level employees, crowded in Social Reference Center of Specialized Assistance (CREAS) and the Migrant Assistance Unit (UAM), and other professionals who participated the Working Group on Homelessness or who were involved with the issue of care of nomadism, and townspeople who were present and participated directly and indirectly in the search, allowing observe the practices and discourses that are construct for roamers who come in town and people on the streets who insist on staying in the squares. The program took place...

A atenção dispensada pelos agentes públicos aos trecheiros e pessoas em situação de rua é cada vez mais crescente subsidiada por um arsenal de normas, orientações, estratégias, instituições, profissionais, políticas, para dar conta das várias facetas da vida nômade e citadina. Por esse motivo, a pesquisa teve como objetivo principal investigar a maneira como esses agentes encarregados dos serviços públicos de assistência social lidavam com trecheiros e pessoas em situação de rua e concebiam esse modo de vida. Interessou, sobretudo, identificar práticas e intervenções no modo de vida de trecheiros e pessoas em situação de rua que procuravam desqualificar a nomadismo ou que o tomava como um modo de vida condenável ou que gerava sofrimentos e que, portanto, precisava ser evitado. Interessou, ainda, compreender como, pelo olhar dos profissionais da assistência social, se produz a figura do indesejável, do estrangeiro, que precisa ser deslocado para outros espaços por meio de políticas públicas de assistência. A pesquisa ocorreu em uma cidade com aproximadamente cem mil habitantes na região oeste do Estado de São Paulo. Essa cidade está localizada num importante corredor de circulação de trecheiros, formado pelo cruzamento de rodovias tronco que ligam o norte do Estado ao Paraná e a região oeste do Estado à região leste, na qual está situada capital. A metodologia empregada foi a etnografia em Psicologia com observação participante. Acompanhamos o trabalho da equipe do município, constituída por assistentes sociais, psicólogos e funcionários de nível médio, lotada no Centro de Referência Especializada de Assistência Social (CREAS) e na Unidade de Assistência ao Migrante (UAM), bem como de outros profissionais que participaram do Grupo de Trabalho de População de Rua ou que estavam envolvidos com a questão da atenção do nomadismo, além de citadinos...
Keywords: Psicologia social; Nômades; Servidores públicos; Public officers